Sistema eletrônico de iluminação para LEDs de estágio único baseado no retificador bridgeless requerendo reduzida tensão de barramento - Holler, Bruno Miguel (2024)
This work presents a topology of static electrical energy converter with the purpose of activating LED lamps. The structure is based on a bridgeless totem pole rectifier, integrated with a half-bridge inverter, which reduces the number of diodes in the input stage and performs power factor correction, but without presenting the voltage doubler characteristic commonly found in these devices. circuits. The system is characterized by three parts: input stage, output stage and the bus. The input stage consists of a charge-pump capacitor, connected in parallel with one of the rectifier diodes, which acts in the circuit to avoid high bus voltage in addition to minimizing current ripple over the LEDs. The output stage consists of a full-wave rectifier circuit with capacitive filter and the LED load. The rectifier circuit converts the alternating current imposed by the input power supply into a direct current to power the LED load. The output stage is connected in series with one of the windings of a coupled inductor that has the function of limiting the LED current in addition to ensuring power factor correction. The bus consists of the half-bridge inverter, a bus capacitor, one of the coupled inductor windings and a resonant capacitor. The resonant capacitor works together with the coupled inductor so that the converter operates with a bus voltage close to the peak value of the input voltage in addition to improving the power factor correction. The integration between the input stage and the bus is carried out by the output stage, where the interaction between the coupled inductor and the charge-pump and resonant capacitor characterize the system as a single stage. The proposed converter has high efficiency and high power factor, in addition to reduced THD, meeting the IEC 61000-3-2 Class C standard. Due to the low ripple in the output current, it also meets the recommendations of IEEE Std 1789-2015. The operating modes and steps are presented, as well as the equation for maximum power transfer. The validation of the equation occurs through the project at 127 V and 175 V, simulated and implemented in practice through the construction of the prototype. The topology, in addition to the advantages already mentioned, presents the possibility of dimming from 100% to 10% of the output power by controlling the LED current.